2017
DOI: 10.3389/fpsyg.2017.01103
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Relation between Early Numerical Competencies and Mathematics Achievement in First Grade Portuguese Children

Abstract: Early numerical competencies (ENC) (counting, number relations, and basic arithmetic operations) have a central position in the initial learning of mathematics, and their assessment is useful for predicting later mathematics achievement. Using a regression model, this study aims to analyze the correlational and predictive evidence between ENC and mathematics achievement in first grade Portuguese children (n = 123). The children’s ENC were examined at the point of school entry. Three criterion groups (low, mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…It could be possible that students’ have better achievement in subjects that their parents care about more. Studies have indicated that the knowledge of mathematics, as a strong foundation for student’s future academic performance, plays an important part in the educational development of youths [ 11 , 12 , 13 , 14 , 15 ]. Additionally, it is well known that mathematics can be regarded as an indispensable skill in all facets of life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It could be possible that students’ have better achievement in subjects that their parents care about more. Studies have indicated that the knowledge of mathematics, as a strong foundation for student’s future academic performance, plays an important part in the educational development of youths [ 11 , 12 , 13 , 14 , 15 ]. Additionally, it is well known that mathematics can be regarded as an indispensable skill in all facets of life.…”
Section: Introductionmentioning
confidence: 99%
“…Parents may focus more on sharing the affective experience of caring about school than academic achievement [ 17 , 26 ]. Further, as mentioned before, the knowledge of mathematics, which is a strong foundation for a student’s future academic performance, plays an important part in a youth’s educational development [ 11 , 12 , 13 , 14 , 27 ]. Therefore, it is advisable to consider the relationship between the various facets of parental involvement and mathematics achievement.…”
Section: Introductionmentioning
confidence: 99%
“…These scores indicate that most students in the United States are not able to demonstrate competence in mathematics on this assessment and the data has consistently demonstrated this level of underachievement since the 1990s (NCES, 2022). Given that mastery of basic number operations is a prerequisite skill students need to have success in more advanced mathematics topics (e.g., rational number knowledge, algebraic principles, and word problem solving) these outcome data highlight a critical need for students to receive more support to become proficient with foundational mathematics skills (Fuchs et al, 2016; Marcelino et al, 2017). Moreover, a recent study found that at the beginning of grade 4 computational proficiency had a direct impact on mathematics problem solving for students at the end of fourth grade (Kaskens, et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that basic arithmetic is a good predictor of later school mathematics achievement (e.g. Marcelino, de Sousa, and Lopes, 2017;Hornung, Schiltz, Brunner, and Martin, 2014). Improving numeracy will lead to better individual perspectives and substantially impact society (OECD, 2018), especially with lower-achieving learners, such as children with special needs.…”
Section: Introductionmentioning
confidence: 99%